PENERAPAN STRATEGI PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES PADA MATA PELAJARAN AKIDAH AKHLAK - Moh Abdur Ro'uf (UNISAN JURNAL, 2024)
The point of this exploration is to analyze in more profundity the Learning Methodology for Islamic Strict Schooling In view of Numerous Insights. This work was composed in light of scholarly experiences and top to bottom comprehension as well as aggregated understanding from different believed essential book sources. This sort of exploration is subjective with a library research approach. Information assortment procedures are completed utilizing documentation. Information sources come from books and diaries. The information investigation strategy utilizes content examination. The examination results show that from the clarification above it tends to be reasoned that learning procedures in view of different insights are difficult. Knowledge comprises of three parts, in particular: the capacity to immediate, the capacity to think or act, the capacity to steer activity when the activity has been done, and the capacity to condemn oneself. The execution of various knowledge learning is by understanding ideas through composition and perusing by joining a few insights including phonetic, intrapersonal, relational and sensation. Kinds of human insight include: Phonetic Knowledge, Legitimate Numerical Insight, Spatial Insight, Substantial Sensation Knowledge, Melodic Insight, Intrapersonal Insight, and Ecological/Regular Insight. Melodic Insight (Melodic Knowledge), Melodic Knowledge (Melodic Knowledge), Intrapersonal Knowledge (Intrapersonal Knowledge) and Ecological/Regular Insight (Naturalist Insight)